2019
DOI: 10.1016/j.celrep.2019.02.039
|View full text |Cite|
|
Sign up to set email alerts
|

Mitofusin 2 in Mature Adipocytes Controls Adiposity and Body Weight

Abstract: SUMMARY We found that exposure of adult animals to caloriedense foods rapidly abolished expression of mitofusin 2 (Mfn2), a gene promoting mitochondrial fusion and mitochondrion-endoplasmic reticulum interactions, in white and brown fat. Mfn2 mRN was also robustly lower in obese human subjects compared with lean controls. Adipocyte-specific knockdown of Mfn2 in adult mice led to increased food intake, adiposity, and impaired glucose metabolism on standard chow as well as on a diet with high calorie content. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 43 publications
1
35
1
Order By: Relevance
“…In addition, mitochondrial fission by protein kinase A (PKA)-dependent phosphorylation of DRP1 at serine 600 is essential for the thermogenesis of the brown adipocytes, and impairment of this regulatory pathway disrupts brown adipocyte function [70]. It has been reported that reduced expression of MFN2 is associated with the reduced function of mitochondria in subcutaneous and visceral adipose tissues of obese subjects [109]. Furthermore, adipocyte-selective inducible deletion of Mfn2 in mice leads to obesity and insulin resistance [109].…”
Section: Mitochondrial Dysfunction In Adipocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, mitochondrial fission by protein kinase A (PKA)-dependent phosphorylation of DRP1 at serine 600 is essential for the thermogenesis of the brown adipocytes, and impairment of this regulatory pathway disrupts brown adipocyte function [70]. It has been reported that reduced expression of MFN2 is associated with the reduced function of mitochondria in subcutaneous and visceral adipose tissues of obese subjects [109]. Furthermore, adipocyte-selective inducible deletion of Mfn2 in mice leads to obesity and insulin resistance [109].…”
Section: Mitochondrial Dysfunction In Adipocytesmentioning
confidence: 99%
“…It has been reported that reduced expression of MFN2 is associated with the reduced function of mitochondria in subcutaneous and visceral adipose tissues of obese subjects [109]. Furthermore, adipocyte-selective inducible deletion of Mfn2 in mice leads to obesity and insulin resistance [109]. The role of mitochondrial dynamics in adipocyte metabolism has not been thoroughly elucidated, and further studies are required to understand the novel regulatory mechanisms of mitochondria in adipocytes.…”
Section: Mitochondrial Dysfunction In Adipocytesmentioning
confidence: 99%
“…Several transcriptional factors including PPARα, PPARδ and PPARγ in the skeletal muscle involved in enhancing insulin sensitivity, glucose tolerance, energy expenditure, and lipid metabolism . Activation of these transcriptional factors enhanced mitochondrial biogenesis leads to dramatically increased endurance, ameliorated insulin resistance in obesity, and type 2 diabetes . It has been known that mitochondrial dysfunction and cellular oxidative stress induced by excess energy states and elevations in circulating free fatty acid (FFA) are associated with insulin resistance in skeletal muscle .…”
Section: Introductionmentioning
confidence: 99%
“…27 It has been reported that Mfn2 knockout or mutation impairs thermogenesis of brown adipocytes, promotes adiposity, and leads to type 2A Charcot-Marie-Tooth disease. [28][29][30] In cultured muscle cells, Mfn2 has been reported to modulate cell respiration, substrate oxidation, and expression of oxidative phosphorylation subunit proteins. 24 In C2C12 and L6E9 myoblast cell lines, Mfn2 levels increase after differentiation, to promote mitochondrial activity and facilitate myocyte fusion.…”
Section: Introductionmentioning
confidence: 99%